An integrated modeling for simultaneous energy recovery and carbon emission reduction for palm oil refining - Woon, Kok Sin, 1986-, author; Haslenda Hashim, supervisor; Fakulti Kejuruteraan Kimia dan Kejuruteraan Sumber Asli (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2009)
Project Paper (Sarjana Muda Kejuruteraan (Kimia) - Universiti Teknologi Malaysia, 2009